Food Processing at a Crossroad - Knorr, Dietrich; Watzke, Heribert (Frontiers in Nutrition, 2019)
Recently, processed foods received negative images among consumers and experts regarding food-health imbalance. This stresses the importance of the food processing—nutrition interface and its relevance within the diet-health debates. In this review, we approach the related questions in a 3-fold way. Pointing out the distinguished role food processing has played in the development of the human condition and during its 1.7 million year old history, we show the function of food processing for the general design principles of food products. Secondly, a detailed analysis of consumer related design principles and processing reveals questions remaining from the historical transformation from basic cooking into advanced food technology. As a consequence, we analyze new and emerging technologies in relation to their contributions to food-health impacts. During the last 35 years, new and emerging food technologies have initiated a paradigm shift away from conventional process methodologies to gentler, non-thermal processing. Reducing the existing uncertainties in the assessment of impact of technology like “minimal processing,” we propose the use of the newly established ISO standard for natural food ingredients as a “reference point.” Finally, we assess the usefulness of recently proposed classification systems, e.g., NOVA classification, based on comprehensive insights of recently published nutritional analysis of those classifications. This paper calls for a radical change and worldwide adaptation of the key research and developmental areas tackling the grand challenges in our food systems.